(untitled) (Journal of Asian Development Studies, 2025)
This study examines spatial variations in vegetation within a fragmented forest ecosystem, investigating the impact of forest fragmentation on biodiversity and ecological processes at Kahuta forest. A stratified random sampling technique was employed, with data collected on vegetation parameters in five elevation zones. Transects were used, each with five 10 x 10 meter sample plots, totalling 25 plots. Elevation, slope, aspect, and coordinates were recorded, and species identified. Parameters studied included frequency, cover, density, and IVI as statistical index, and ANOVA applied. The study gives crucial information on plant communities in various zones and elevations. Pinus roxburghii is the dominant species throughout all zones, with the highest IVI. In zone III, Olea ferruginea plays a significant role. Acacia modesta, Cassia fistula, and Morus alba all make significant contributions. Shrubs that contribute to biodiversity include Dodonea viscosa, Carica opaca, and Agave sisalana. To compare ecological parameters from zone I to zone V along an altitudinal gradient to compare the mean scores of different species within each zone. The findings indicated significant differences in group means, with p-values significantly lower than the conventional 0.05 significance level, indicating that the observed variances were statistically significant. These findings highlight the ecological significance of altitude and species interactions in shaping plant communities within the examined region.